PENGARUH PROGRAM PELATIHAN KECEPATAN (SPEED) TERHADAP AKSELERASI DAN KECEPATAN MAKSIMUM - Teguh Andibowo; Kodrad Budiyono; Hartini; Erik Teguh Prakosa; Ardya Resti Prasasti (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
The aim of this research is to analyze about: ( 1 ) the influence, training programs speed acceleration in football player against the increasing; ( 2 ) influence training programs to speed the maximum speed on football player; and ( 3 ) the difference influence a training program to increasing speed and acceleration of maximum speed on football player.This research is football SSB Safo Jomblo selection with a total sample of 22 athletes. This type of research used in this study is a quantitative quasi-experimental methods. The design of this study used only matching design, and data analysis using Manova. The process of data collection was done with a test run of 30 meters for acceleration and run of 30 meters tests for maximum speed at the time of the pretest and posttest. Furthermore, the data were analyzed using SPSS 19.0 series. The results showed: (1) there is a significant influence on the speed of accelerated training programme on football player; (2) there is a significant effect of speed training program to increase maximum speed on soccer player; (3) there is a difference between training programs effect the speed of increase in acceleration and maximum speed on the soccer players. Based on the above analysis, it can be inferred that there is an increase in acceleration and maximum speed for experimental group and the control group after being given training speed from the results of the t-test.